Wearable and stretchable electronics enabled by MXene–PVA films via layer-by-layer assembly with integrated UV, thermal, and mechanical sensing - Lin, Ji; Chang, Chia-Wei; Chang, Chun-Ting; Manibalan, Kesavan; Tsai, Tsung-Hung; Lin, Yu-Chun; Hsu, Yen-Shen; Chang, Ming-Hsuan; Chen, Jiun-Tai (Chemical communications (Cambridge, England), 2025)
We integrate MXene with polyvinyl alcohol (PVA) through a meticulous layer-by-layer assembly process, not only enhancing the mechanical flexibility and robustness of MXene but also significantly improving its environmental stability. The MX–PVA films exhibit multi-responsiveness to UV light, temperature, and mechanical pressure, highlighting their potential for use in wearable electronics.